2011
DOI: 10.1111/j.1399-3046.2011.01507.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of renal transplantation in children: A multi‐center national report from Iran

Abstract: The outcome of pediatric renal transplantation was previously reported by a single-center study at the year 2006. Therefore, we aimed to evaluate and report the characteristics and outcome of renal pediatric renal transplantation in a multi-center nationwide study. In this nationwide report, medical records of 907 children (≤18yr) with renal transplantation in eight major pediatric transplant centers of Iran were recorded. These 907 patients received a total of 922 transplants. All children who failed to follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The NAPRTCS registry data show 1‐ and 5‐year graft survival rates of 95.5% and 85.7% (1995‐2010) in living‐donor pediatric KT 13 . The outcome of KT in this study is better than previous pediatric reports 5,27,44 . Our 1, 3, 5, and 10 graft/patient survival rates are 91.9%, 91.8%, 89.2%, and 58.3%, respectively.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…The NAPRTCS registry data show 1‐ and 5‐year graft survival rates of 95.5% and 85.7% (1995‐2010) in living‐donor pediatric KT 13 . The outcome of KT in this study is better than previous pediatric reports 5,27,44 . Our 1, 3, 5, and 10 graft/patient survival rates are 91.9%, 91.8%, 89.2%, and 58.3%, respectively.…”
Section: Discussionmentioning
confidence: 44%
“…It was reported that episodes of AR are associated with poor long‐term survival rates 11,27,28 . In our series; a total of 48 patients developed at least one AR episode during 688 patient‐years of follow‐up (7% per patient‐year overall and 4.4% after the first year).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…This compares favourably to published long-term outcome from national and regional registries. The published studies on the outcome of paediatric renal transplants are summarised in Table 4 [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…A remarkable finding in our cohort was the exceedingly high rate (64%) of early graft dysfunction in those with recurrent FSGS, which is 2.5‐fold higher than in nonrecurrent FSGS and 5‐fold higher compared to the general pediatric NIKTR data. The reported early graft dysfunction rate is 5–10% in pediatric KT . The differential diagnosis in this condition usually includes acute tubular necrosis (ATN) and acute rejection.…”
Section: Discussionmentioning
confidence: 99%